FACTORS RELATED TO SELF-EFFICACY AND ACADEMIC PROCRASTINATION AMONG FINAL-YEAR STUDENTS AFTER DISTANCE LEARNING - Solihin, Muhtar Mochamad (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Post-distance learning final year students have more challenges than ever before. This study aims to analyze: 1) the characteristics of final year students, 2) the level of self-efficacy and academic procrastination of students, and 3) the factors associated with self-efficacy and academic procrastination of post-distance learning students. This research approach is quantitative with survey method. Respondents were 97 students at the Islamic college. Data were collected using an online questionnaire. The results showed that: 1) the characteristics of respondents are generation Z groups (digital natives), are preparing a thesis and almost half of the respondents only focus on activities to complete their studies, 2) the level of self-efficacy and academic procrastination of respondents is moderate tends to be high, and 3) factors related to self-efficacy are age, amount of pocket money and information literacy, while factors related to academic procrastination are age and duration of internet access. Therefore, students need to increase self-efficacy and reduce procrastination in completing the thesis.